2017
DOI: 10.1007/s00003-017-1113-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and isolation of Shiga-Toxin producing Escherichia coli in flour in Germany between 2014 and 2017

Abstract: Official control samples of wheat and rye flour were analyzed for the presence of Shiga-toxin producing Escherichia coli (STEC) in 25 g. The detection procedure was based on enrichment in buffered peptone water and Tryptone Bile X-Glucuronide agar, followed by multiplex real-time PCR with an internal positive control. Positive samples were sub-cultured for strain isolation by a two-step procedure. In the first step, ten colonies were picked from each plate, pooled, and analyzed by real-time PCR. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A recent report suggests that the frequency and level of flour contamination may be much higher than previously believed (Mäde et al, 2017). The presence of pathogenic bacteria poses a serious risk to consumers because of cross contamination or consumers handling habits such as ingesting raw cookie dough (Rose et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…A recent report suggests that the frequency and level of flour contamination may be much higher than previously believed (Mäde et al, 2017). The presence of pathogenic bacteria poses a serious risk to consumers because of cross contamination or consumers handling habits such as ingesting raw cookie dough (Rose et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, Camino Feltes, Arisseto‐Bragotto, and Block () documented that it is one of the commonly known agents which causes diarrhea, abdominal pain, vomiting, and/or nausea. Mäde, Geuthner, Imming, and Wicke () and de Quadros Rodrigues et al () independently confirmed the prevalence of E. coli in cereals and legumes.…”
Section: Resultsmentioning
confidence: 83%
“…A study has suggested that the level of STEC in contaminated flour samples were below 1 MPN/100g (23). Another study results revealed that isolation of STEC was independent on the presence of generic E. coli of flour samples (34). Therefore, it is not surprising that non-O157 STEC positive samples had generic E. coli below the limit of detection (<0.48 log CFU/g).…”
Section: Stec Enrichment Identification Isolation and Characterizatmentioning
confidence: 99%
“…Wheat flour is an agricultural product which can be contaminated with bacterial pathogens during primary production and the milling process (34,37). The low-moisture content (aw <0.6) of wheat flour does not support the growth of bacterial pathogens, however some bacterial pathogens can survive in this low-moisture environment (21,25) and can multiply in highermoisture raw flour-based products such as batter or cookie dough (43).…”
Section: Highlightsmentioning
confidence: 99%